2013
DOI: 10.1371/journal.pone.0072468
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Galectin-7 Is Induced in Breast Cancer Cells by Mutant p53

Abstract: Galectin-7 was initially described as a marker of epithelial differentiation expressed in the stratified epithelium of various tissues. Like other members of the galectin family, its expression level is often significantly altered in cancer cells. In breast cancer, its expression is significantly augmented in aggressive molecular subtypes, most notably in estrogen receptor-negative tumors and in cell lines with a basal-like phenotype. Studies using experimental mouse models have further shown high expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 34 publications
(39 reference statements)
1
41
0
1
Order By: Relevance
“…The ability of C/EBPβ to displace NF-κB on the galectin-7 promoter was confirmed by ChIP analysis which showed that while endogenous p50 is constitutively bound to the galectin-7 promoter, transfection of C/EBPβ-2 displaced the p50 homodimers, leading to a strong activation of galectin-7 expression. However, in presence of transcriptionally active NF-κB complexes, containing c-Rel for example, NF-κB could possibly exert a positive influence of galectin-7 expression, as we recently showed [38]. In other words, galectin-7 expression in cancer cells with an inactive p53 pathway possibly involves C/EBP and/or NF-κB.…”
Section: Discussionmentioning
confidence: 80%
“…The ability of C/EBPβ to displace NF-κB on the galectin-7 promoter was confirmed by ChIP analysis which showed that while endogenous p50 is constitutively bound to the galectin-7 promoter, transfection of C/EBPβ-2 displaced the p50 homodimers, leading to a strong activation of galectin-7 expression. However, in presence of transcriptionally active NF-κB complexes, containing c-Rel for example, NF-κB could possibly exert a positive influence of galectin-7 expression, as we recently showed [38]. In other words, galectin-7 expression in cancer cells with an inactive p53 pathway possibly involves C/EBP and/or NF-κB.…”
Section: Discussionmentioning
confidence: 80%
“…Since both p53 and NF-jB belong to stress-induced transcription factors, the corresponding upregulation of galectin-7 should be considered in the context of specific cellular stress responses with differential outcomes, which fits perfectly with the conceptual paradigm of stress-induced selection between cell death or cell survival. Indeed, the biological role of galectin-7 cannot be solely related to its pro-apoptotic functions due to the crosstalk between both p53 and NF-jB, as recently demonstrated in MCF7 breast cancer cells [65]. In addition, recent studies have revealed that the upregulation of galectin-7 in breast cancer cell lines MCF7 and MDA-MB-231 is driven by C/EBPb-2, which can explain the paradox of concomitant galectin-7 overexpression in cancer cells and p53 mutation [66].…”
Section: Galectin-7mentioning
confidence: 97%
“…The target genes of TP53 mutant/TFs complexes are quite diverse in terms of their biological effects comprising genes that stimulate proliferation, inhibit apoptosis, promote chemoresistance, and influence EMT transition [Brosh and Rotter, ; Liu et al., ; Kogan‐Sakin et al., ; Freed‐Pastor and Prives, and reference therein; Kalo et al., ; Noll et al., ; Vaughan et al., ; Campion et al., ; Garritano et al., ]. These genes include, among others, c‐MYC [Frazier et al., ], PCNA (Proliferating Cell Nuclear Antigen), hTERT (human Telomerase Reverse Transcriptase)[Scian et al., ], ASNS (Asparagine Synthetase) [Scian et al., ], EGFR , EGR1 (Early Growth Response 1) [Weisz et al., ], and ABCB1 (Multi Drug Resistance‐1), the first gene discovered as TP53 mutant target [Chin et al., ].…”
Section: Gof Properties Of Cancer‐associated Tp53 Mutantsmentioning
confidence: 99%